First Do No Harm A Chemist's Guide to Molecular Design for Reduced Hazard - Petrovic, Predrag V. (Jenny Stanford Publishing, 2023)
This book is the first to provide chemists with useful, practical guidance on how to minimize or avoid a wide range of hazards. Building on the insights gained from the pharmaceutical industry over the past 25 years on how to create desirable biological effects, the authors demonstrate how to avoid undesirable biological effects by design
Description based on publisher supplied metadata and other sources
Keywords: Green chemistry; Grüne Chemie